The FRA Corpus from the DISease and AGEing Project - Dovetto, Francesca M.; Marra, Francesca (Journal of Language and Aging Research, 2024)
The FRA corpus, from the DISAGE project (University of Naples Federico II), is an Italian speech corpus of elderly people with and without neurodegenerative pathologies. The project's main aim is to provide an Italian tool useful to observe language in pathological aging. Therefore, the project enrolled 20 patients diagnosed with Alzheimer's Disease (AD), 20 individuals suffering from Mild Cognitive Impairment (MCI), and 20 Healthy Controls (HC) balanced with respect to sex, age, and education. Participants underwent neuro-psychological testing (MMSE; Raven's Matrices) and only mild AD and amnestic MCI were recruited. The speech corpus is semi-spontaneous and dialogic: speech samples were collected via a three-stage interview designed to encourage the production of descriptive, conversational and narrative speech. Currently, 18 out of the 60 recordings collected have been manually and orthographically transcribed. Data is available on request.